Photos vs silhouettes for evaluation of profile esthetics between white and black evaluators - Pithon, Matheus Melo; Silva, Iane Souza Nery; Almeida, Indira Oliveira; Nery, Marine Soares; de Souza, Michele Luz; Barbosa, George; dos Santos, Alex Ferreira; da Silva Coqueiro, Raildo (The Angle orthodontist, 2014)
To determine whether photos or silhouettes are adequate methods for evaluating the esthetic profiles of black subjects and whether black and white evaluators have different preferences for esthetic profiles. One photographic record of the profile of a black female patient with accentuated dental bimaxillary dentoalveolar protrusion was randomly selected. The image of the patient's profile was altered to produce a series of seven photos and seven silhouettes (a total of 14 images) with different lip positions but uniform distances in relation to the esthetic plane created by Ricketts (line E). Fifty black and 50 white lay evaluators were invited to enumerate the photos and silhouettes, produced according to the lip position, in the order in which they considered most esthetically pleasing. The number of preferences found to be within the esthetic norm was slightly higher among the photographs than among the silhouettes; the esthetic profile with a deviation of -2 mm from line E was elected as the most attractive, and the esthetic pattern with a deviation of +6 mm from the normal line E was considered the least attractive. There were no statistically significant differences between the preferences related to the variables race, sex, and educational background. The esthetic attractiveness of the facial profiles of black subjects in photos and silhouettes was evaluated in a similar manner among black and white evaluators. Among both black and white evaluators, the greatest preference was for the slightly concave profile, which was within the limit considered standard.